Does the Democracy and Economic Growth Affect Human Development in Indonesia? - Soeparno, Wahyu Sugeng Imam; Pratomo, Wahyu Ario (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2023)
Democracy and economic growth can be improvement of human development progress. The interaction between democracy and economic growth and human development achievements has profound implications for the development of societies and countries. This article will contribute to a better understanding of the complicated interplay between democracy, economic growth and human development. The study employs the autoregressive distributed (ARDL) to prove the relationship between democracy, economic growth and human development in Indonesia for the period 1990-2021. There is long-run cointegration relationship between democracy and economic growth on human development in Indonesia during the sample period. Where, economic growth contibutes positively to HDI and is statistically significant and democracy not significant impact to human development in Indonesia. In the short-run, democracy and economic growth have a positive and significant impact on human development in Indonesia. where democracy has greater implications for human development than economic growth. Diagnostic tests for serial correlation, functional form, normality and heteroscedasticity of the models were conducted, and the results are valid for meaningful interpretation.